Mycotoxins: Simultaneous Detection of Zearalenone and Citrinin by Voltammetry on Edge Plane Pyrolytic Graphite Electrode. Issue 9 (6th August 2014) - Nasir, Muhammad Zafir Mohamad; Pumera, Martin
Abstract Mycotoxins are highly toxic compounds often found in the food. It is of paramount importance to have analytical technique for point‐of‐care on‐spot detection for authorised personnel to immediately take the action required. Electrochemistry offers the portability for miniaturized sensor of mycotoxins. Here we show that edge‐plane pyrolytic electrode offers excellent selectivity and sensitivity towards simultaneous detection of zearalenone and citrinin. This will have a great impact for point‐of‐care mycotoxin detection.